2021
DOI: 10.1039/d0fd00134a
|View full text |Cite
|
Sign up to set email alerts
|

Renewable carbon feedstock for polymers: environmental benefits from synergistic use of biomass and CO2

Abstract: Polymer production is a major source of greenhouse gas (GHG) emissions. To reduce GHG emissions, the polymer industry needs to shift towards renewable carbon feedstocks such as biomass and CO2....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…17 Within the eld of polyurethane, nding suitable bio-renewable raw materials to replace petroleum-based polyols has become the focus of research. [18][19][20][21] With the intensive research on the high value of bio-based materials, plant oil has become the important research target for petroleum-based polyol alternatives due to its widely sources, low price, recyclability and convenient to production. 22 It has been found that bio-based polyols prepared from plant oils can effectively regulate the properties of polyurethane foams by replacing fossil-based polyols.…”
Section: Introductionmentioning
confidence: 99%
“…17 Within the eld of polyurethane, nding suitable bio-renewable raw materials to replace petroleum-based polyols has become the focus of research. [18][19][20][21] With the intensive research on the high value of bio-based materials, plant oil has become the important research target for petroleum-based polyol alternatives due to its widely sources, low price, recyclability and convenient to production. 22 It has been found that bio-based polyols prepared from plant oils can effectively regulate the properties of polyurethane foams by replacing fossil-based polyols.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that CCS projects might be limited by the geological conditions surrounding the targeting ethanol plant, the utilization of CO 2 for commercial products (CCU) can be another option. One of the promising CCU pathways identified in previous studies is the conversion of waste CO 2 into methanol, 31–33 because methanol is an important chemical with wide applications (e.g., biofuel, polymers). In this study, we modeled synthetic methanol production using CO 2 captured from ethanol fermentation and renewable H 2 produced through electrolysis using wind and solar power.…”
Section: Methodsmentioning
confidence: 99%
“…128 One less developed, but still potential, renewable feedstock for plastic, is captured carbon dioxide, 129,130 which could also be synergistically used with bio-based production processes. 131 The source and substitution effect of the captured CO 2 are crucial when estimating the climate impact and mitigation potential of such processes. 132 Another niche technology with growing expectations is (green) hydrogen, which can be used both as a feedstock and energy source.…”
Section: Bio-based and Alternative Feedstock-a Bioeconomymentioning
confidence: 99%